Testosterone and breast cancer prevention. Issue 3 (November 2015) - Glaser, R.; Dimitrakakis, C.
Highlights: Testosterone is essential for mental and physical health in women including breast cancer survivors. Evidence supports that testosterone is breast protective but is aromatized to E2. Diet and lifestyle are modifiable factors, which affect overall health, aromatase activity, hormone balance, and subsequently, breast cancer risk. Testosterone alone or with an aromatase inhibitor should be investigated further for hormone therapy as well as for prevention and therapy of breast cancer. Abstract: Testosterone (T) is the most abundant biologically active hormone in women. Androgen receptors (AR) are located throughout the body including the breast where T decreases tissue proliferation. However, T can be aromatized to estradiol (E2), which increases proliferation and hence, breast cancer (BCA) risk. Increased aromatase expression and an imbalance in the ratio of stimulatory estrogens to protective androgens impacts breast homeostasis. Recent clinical data supports a role for T in BCA prevention. Women with symptoms of hormone deficiency treated with pharmacological doses of T alone or in combination with anastrozole (A), delivered by subcutaneous implants, had a reduced incidence of BCA. In addition, T combined with A effectively treated symptoms of hormone deficiency in BCA survivors and was not associated with recurrent disease. Most notably, T + A implants placed in breast tissue surrounding malignant tumors significantly reduced BCA tumor size, further supporting T direct antiproliferative, protective and therapeutic effect.